Efficacy and Tolerability of Two Quadruple Regimens: Bismuth, Omeprazole, Metronidazole with Amoxicillin or Tetracycline as First-Line Treatment for Eradication of Helicobacter Pylori in Patients with Duodenal Ulcer: A Randomized Clinical Trial. - Hassan Salmanroghani (PLoS ONE, 2018)
AIM:To evaluate the efficacy and tolerability of tetracycline vs. high-dose amoxicillin in bismuth-based quadruple therapy for Helicobacter pylori(H. pylori) eradication. METHODS:This randomized, open-label clinical trial included 228 patients with H.pylori infection and duodenal ulcer without a history of H.pylori treatment. Patients were randomly divided into two groups. The amoxicillin group received metronidazole 500mg, bismuth subcitrate 240mg, and amoxicillin 1000mg, all three times a day, plus omeprazole 20 mg twice a day, for 14 days. The tetracycline group received metronidazole 500mg three times a day; bismuth subcitrate240mg and tetracycline HCl 500mg, both four times a day; and omeprazole 20 mg twice a day, for 14 days. Evaluation for compliance and drug-relatedadverse effects were evaluated at the end of two weeks. Eight weeks after the end of treatment, the rate of H.pylori eradication was assessed by the C13urease breath test. RESULTS:There were no significant demographic differences between the two groups. Eradication rate was higher with the amoxicillin-containing regimen than the tetracycline-containing regimen: 105/110 (95.51%; 95% confidence interval, 91.5%-99.3%) vs. 88/105 (83.8%; 95%CI, 76.7%-90.8%) by per-protocol analysis (p = 0.005) and 92.9% (95%CI, 88.1%-97.6%) vs. 76.5% (95%CI, 68.7%-84.2%) by intention-to-treat analysis (ITT, p = 0.001). Adverse effects were significant higher in the tetracycline groupthan in the amoxicillin group (65.2% vs. 43.4%; p = 0.001). CONCLUSION:Bismuth-based quadruple therapy including high-dose amoxicillin and metronidazole achieved an acceptable rate of H.pylori infection eradication with good tolerance in patients with duodenal ulcer. This regimen can overcome treatment resistance in areas with high prevalence of metronidazole and clarithromycin resistance. TRIAL REGISTRATION:The Thai Clinical Trial Registry (TCTR) 20170623004.